Effects of different hijab fabrics on image quality in skull x-ray using computed radiography - Tamson, Nuramisha Diana; Jamaludin, Iqbal (IIUM Press, International Islamic University Malaysia, 2024)
Background: Covering the aurah in Islam is considered a sign of respect, dignity, and privacy. In skull x-ray examination, female patients often feel uncomfortable when being requested to remove their hijab for skull x-ray examination. Therefore, this study aims to evaluate the effects on radiographic image quality in PA (0°) skull x-ray examination when using different types of hijab materials. Methods: This study is conducted by using the skull part of Kyoto Kagaku phantom, with the help of immobilisation aids. The phantom is exposed without hijab at optimum exposure factor that is used as a reference image, and been compared with the image quality produced by the x-ray examination using three different hijab materials. Each hijab materials (Premium Chiffon Georgette, Premium Valencia Satin and Premium Cotton Rayon) then been exposed together with phantom using three different exposure factors: low (61.5 kVp, 20 mAs), optimum (73 kVp, 10 mAs) and high (83 kVp, 5 mAs). Four experienced observers blindly graded the image quality using Visual Grading Analysis (VGA). Results: The results were analysed by using Kruskal-Wallis to find the effect of different hijab materials on optimum exposure, while Friedman test was used to find any significant findings between different hijab materials and three different exposure factors; low, optimum and high. From the Kruskal-Wallis result, the radiographic image quality of all three hijab materials produce no significant difference when compared with skull x-ray image without hijab. Friedman test found only hijab material of Premium Valencia Satin when exposed with 61.5 kVp 20 mAs (low), 73 kVp 10 mAs (optimum) and 83 kVp 5 mAs (high) to be significant (p-value=0.022). Conclusion: It can be concluded that Premium Chiffon Georgette and Premium Cotton Rayon are suitable to be used in skull x-ray examination as they did not produce any notable artifacts on skull x-ray radiograph, while special consideration must be made for patient wearing hijab material of Premium Valencia Satin that will undergo skull x-ray examination.